Handgrip strength and health outcomes: Umbrella review of systematic reviews with meta-analyses of observational studies - Pinar Soysal; Christopher Hurst; Jacopo Demurtas; Joseph Firth; Reuben Howden; Lin Yang; Mark A. Tully; Ai Koyanagi; Petre Cristian Ilie; Guillermo F. López-Sánchez; Lukas Schwingshackl; Nicola Veronese; et al. (Elsevier, 2021)
Purpose: The aim of the present study was to assess both the credibility and strength of evidence arising from systematic reviews with meta-analyses of observational studies on handgrip strength and health outcomes. Methods: An umbrella review of systematic reviews with meta-analyses of observational studies was conducted. We assessed meta-analyses of observational studies based on random-effect summary effect sizes and their p values, 95% prediction intervals, heterogeneity, small-study effects, and excess significance. We graded the evidence from convincing (Class I) to weak (Class IV). Results: From 504 articles returned in a search of the literature, 8 systematic reviews were included in our review, with a total of 11 outcomes. Overall, nine of the 11 of the outcomes reported nominally significant summary results (p < 0.05), with 4 associations surviving the application of the more stringent p value (p < 10−6). No outcome presented convincing evidence. Three associations showed Class II evidence (i.e., highly suggestive): (1) higher handgrip values at baseline were associated with a minor reduction in mortality risk in the general population (n = 34 studies; sample size = 1,855,817; relative risk = 0.72, 95% confidence interval (95%CI): 0.67-0.78), (2) cardiovascular death risk in mixed populations (n = 15 studies; relative risk = 0.84, 95%CI: 0.78-0.91), and (3) incidence of disability (n = 7 studies; relative risk = 0.76, 95%CI: 0.66-0.87). Conclusion: The present results show that handgrip strength is a useful indicator for general health status and specifically for early all-cause and cardiovascular mortality, as well as disability. To further inform intervention strategies, future research is now required to fully understand mechanisms linking handgrip strength scores to these health outcomes.